2005
DOI: 10.1016/j.jpeds.2005.06.040
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Pathway for Bronchiolitis is Effective in Reducing Readmission Rates

Abstract: A clinical pathway specifying local practice guidelines and discharge criteria can reduce the risk of readmission to hospital, the use of inappropriate therapies, and help with discharge planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 9 publications
1
45
0
7
Order By: Relevance
“…If a combined readmissions measure for common diseases was adopted, potential interventions could focus on delivering guideline-recommended care across similar diseases. Previous studies implementing care pathways and improving compliance with guidelines have reduced pediatric readmissions for bronchiolitis 35 and asthma, 36 although other studies have not shown improvements, 8,37 and thus additional work remains to be done. A pooled measure of readmissions for hospitals that admit a large number of complex chronically ill children, 38 who are known to be at risk for frequent readmissions, 2,3 could focus improvements specifically on these children during their transitions of care.…”
Section: Discussionmentioning
confidence: 99%
“…If a combined readmissions measure for common diseases was adopted, potential interventions could focus on delivering guideline-recommended care across similar diseases. Previous studies implementing care pathways and improving compliance with guidelines have reduced pediatric readmissions for bronchiolitis 35 and asthma, 36 although other studies have not shown improvements, 8,37 and thus additional work remains to be done. A pooled measure of readmissions for hospitals that admit a large number of complex chronically ill children, 38 who are known to be at risk for frequent readmissions, 2,3 could focus improvements specifically on these children during their transitions of care.…”
Section: Discussionmentioning
confidence: 99%
“…Only 3 studies used some form of external control. 29,30,34 The lack of control subjects in before-and-after studies raises concerns that the change reported could have been due to secular trends rather than the intervention described. All studies did well on evaluation of whether the before-and-after study population shared similar characteristics.…”
Section: Methodologic Qualitymentioning
confidence: 99%
“…The characteristics of the 14 studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38] in this review are described in Table 1, including our qualitative assessment of the categorical type of intervention (described later in further detail): primarily educational (providing voluntary guidelines, presenting conferences); involving significant process change (implementing standardized order sets); and involving significant process change plus the use of a respiratory score. A respiratory score was loosely defined as any multicomponent numerical representation of respiratory effort.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 At the hospital level, many institutions have implemented interventions such as clinical pathways or practice guidelines to improve care for children hospitalized for respiratory illnesses. [5][6][7][8][9] However, such interventions require substantial commitment of resources toward development, implementation, and maintenance. 10 Ideally, interventions to improve care should be targeted toward high-risk patients or hospitals.…”
mentioning
confidence: 99%